FOLFOX alone or combined with rilotumumab or panitumumab as first-line treatment for patients with advanced gastroesophageal adenocarcinoma (PRODIGE 17-ACCORD 20-MEGA): a randomised, open-label, three-arm phase II trial. (July 2019) - Malka, David; François, Eric; Penault-Llorca, Frédérique; Castan, Florence; Bouché, Olivier; Bennouna, Jaafar; Ghiringhelli, François; de la Fouchardière, Christelle; Borg, Christophe; Samalin, Emmanuelle; Bachet, Jean-Baptiste; Raoul, Jean-Luc; et al.
Abstract: Background: Epidermal growth factor receptor (EGFR) and hepatocyte growth factor (HGF)/mesenchymal–epithelial transition (MET) pathways, which promote tumour growth and proliferation, are often deregulated in advanced gastroesophageal adenocarcinomas. We assessed whether adding panitumumab (an EGFR inhibitor) or rilotumumab (a HGF inhibitor) to first-line fluoropyrimidine-based and platinum-based chemotherapy (modified oxaliplatin, leucovorin and fluorouracil [mFOLFOX6]) benefits to patients with advanced gastroesophageal adenocarcinoma. Patients and methods: This phase II, open-label, randomised, three-arm study enrolled patients ≥18 years, with advanced gastroesophageal adenocarcinoma, Eastern Cooperative Oncology Group performance status 0–1 and no known HER2 overexpression. Patients were randomly assigned (1:1:1) mFOLFOX6 (oxaliplatin 85 mg/m 2, leucovorin 400 mg/m 2, 5-fluorouracil 400 mg/m 2 bolus then 2400 mg/m 2 over 46 h) alone or combined with panitumumab (6 mg/kg) or rilotumumab (10 mg/kg) every 2 weeks until limiting toxicity, patient's refusal or disease progression. The primary end-point was the 4-month progression-free survival (PFS) rate. Secondary end-points included overall survival (OS) and tolerance. Results: The study enrolled 162 patients in 29 French centres. The median follow-up was 23.6 months (interquartile range = 16.4–29.0). The 4-month PFS rate was 71% (95% confidence interval [CI] = 57–82) with chemotherapy alone, 57% (95% CI = 42–71) combined with panitumumab and 61% (95% CI = 47–74) combined with rilotumumab. Median OS was 13.1 months (95% CI = 8.7–16.9) with chemotherapy alone, 8.3 months (95% CI = 6.2–13.2) combined with panitumumab and 11.5 months (95% CI = 7.9–17.1) combined with rilotumumab. Adverse events grade ≥III occurred less frequently with chemotherapy alone (62%) than with panitumumab (83%) and rilotumumab (89%). Conclusions: We found no benefit in adding panitumumab or rilotumumab to mFOLFOX6 first-line chemotherapy to treat advanced gastroesophageal adenocarcinoma patients. Trial registration: European Clinical Trials Database, number 2009-012797-12. Highlights: Fluoropyrimidine-platinum doublets are the standard for advanced gastric cancer. EGFR and HGF/MET pathways are often deregulated in advanced gastric cancer. Panitumumab and rilotumumab are directed against EGFR and HGF, respectively. Adding panitumumab to chemotherapy is ineffective in advanced gastric cancer. Adding rilotumumab to chemotherapy is ineffective in advanced gastric cancer.